Erratum: Genetic link between renal birth defects and congenital heart disease - Jovenal T. San Agustin (Nature Portfolio, 2016)
Nature Communications 7 Article number:11103 (2016); Published 22 March 2016; Updated 8 June 2016 In Fig. 6 of this Article, defects in the tectonic complex were inadvertently labelled during the production process as causing postnatal, rather than prenatal cysts. The correct version of the figure appears below.